Baseline echocardiographic variables as predictors of hemodynamically significant cytokine release syndrome in adults treated with CD19 CAR T-cell therapy for hematological malignancies - Andres E. Daryanani; Muhannad A. Abbasi; Maria F. Gomez Ardila; Eduardo Tellez-Garcia; Juan M. Garzon-Dangond; Yi Lin; Jonas Paludo; Joerg Herrmann; Stephen M. Ansell; Allison C. Rosenthal; Hector R. Villarraga (Cardio-Oncology)
Abstract Background CD19 CAR T-cell therapy is a novel anti-cancer treatment that has produced remarkable responses in relapsed or refractory B-cell hematological malignancies. Cytokine Release Syndrome (CRS) is a dysregulated immune response that frequently occurs after CAR T-cell infusion. It can cause cardiac dysfunction and circulatory collapse negatively impacting outcomes and survival. To endure the insults of CRS, patients are typically screened for adequate cardiac reserve before treatment. The relationship between baseline cardiac function by echocardiography and the development of moderate to severe presentations of CRS is unclear. Methods This study aimed to identify baseline echocardiographic variables that can predict the development of hemodynamically significant CRS (CRS ≥ 2), evaluate their behavior at follow-up, and investigate the incidence of cancer therapy-related cardiac dysfunction (CTRCD). An observational retrospective cohort study of patients treated with CD19 CAR T-cell therapy with a baseline echocardiogram was performed. Demographic, clinical and echocardiographic variables were abstracted from the electronic health record. Patients were grouped and compared by the occurrence of CRS < 2 and ≥ 2. Adjusted logistic regression analysis was used to evaluate the association between echocardiographic variables and the development of CRS ≥ 2. Results 291 patients were included in the study. Median age was 60 (IQR: 51, 67 years), 73% were male, and 71% had diffuse large B-cell lymphoma. Logistic regression analysis did not reveal any significant baseline echocardiographic predictors of CRS ≥ 2, including left ventricular ejection fraction and global longitudinal strain. Systolic and diastolic echocardiographic variables remained within normal limits at follow-up overall and in both CRS groups. The incidence of CTRCD was 4.5% and occurred mostly in the setting of CRS ≥ 2. Conclusion No specific echocardiographic variables predicted the development of CRS ≥ 2, and therefore the mechanism leading to hemodynamic decompensation and producing worsening hypoxia and hypotension could be multifactorial and not directly cardiac mediated.